Antibiotic resistance in commercially available probiotics in Bangladesh - Rupa, Sadia Islam; Tasnim, Naima (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.